Glove Usage in the Intensive Care Unit - Nimet Ateş; Semra Yurdakul (Galenos Yayinevi, 2022)
Objective:Glove usage is recommended for healthcare professionals to protect themselves and reduce the risk of transmission of biological body fluids that get in contact with their hands from one patient to another. Unnecessary and incorrect usage of gloves increases the risk of cross contamination. This study aimed to evaluate the correct and necessary glove usage in the intensive care unit (ICU) where wearing gloves is not observed.Materials and Methods:This is a prospective, cross-sectional and observational study. The study was made in a third level general ICU of a university hospital. Glove usage practice of physicians, nurses and caregivers working in the ICU were determined by observation method. The "5 necessary moments" was observed in the appropriate glove usage. Wearing of gloves when unnecessary was evaluated as "unnecessary glove usage". Observations were made by the ICU nurse and the infection control nurse.Results:A total of 395 observations were made on glove usage. The rate of appropriate glove usage is 67.8%, and misused gloves are 32.2%. The highest rate of correct glove usage was 86.1% (n=101), which was observed in the event of blood and/or body fluid contact. In the same patient, dirty procedures/changing gloves between different regions (n=68) were not performed. Unnecessary glove usage was observed at a rate of 85.1% (n=74). The distribution of glove usage by profession was statistically significant (chi-square: 44.15, p<0.001); however, it was not significant according to gender (chi-square: 2.13, p<0.144).Conclusion:Systematic observation of glove usage provided an appropriate evaluation, thus studies about necessary glove usage should be carried out to determine the reasons for healthcare professionals' behaviour in using gloves to improve correct glove usage and prevent its unnecessary usage.